ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY ON EMPLOYEE PERFORMANCE THROUGH WORK DISCIPLINE: A CASE STUDY AT PT. ASURANSI TAKAFUL KELUARGA, MEDAN BRANCH - Rahman, Abdul; Syahriza, Rahmi (MAP Observer: Jurnal Penelitian Administrasi Publik, 2025)
Human resources or employees owned by a company undoubtedly influence the company's performance. High-quality human resources will have a positive impact by contributing to optimal performance. Therefore, every company sets certain criteria that must be met by its employees. However, improving company performance cannot be achieved solely by hiring competent employees; it also requires individuals with high motivation and strong work discipline. Motivation and work discipline are among the factors that can affect employee performance. This study aims to examine the direct influence of motivation on employee performance and to explain the indirect influence of motivation on performance through work discipline.